The Role Of Women In The Development Of Health Care In Uzbekistan - Teshayeva Sitora (Academia One Publishing, 2024)
Today, scientific research centers and higher education institutions specializing in the field of medicine of various leading countries of the world are conducting a number of scientific researches aimed at studying various directions of the field of medicine
Keywords: World Health Organization; women; PhD; professor